Parents Roles In Supporting Students To Learn English From Home During Pandemic Covid-19 - Triznawasti Yuditha Daik; Adolfina M.S. Moybeka; Agustina Aloojaha; Hartini Baso (Peneliti.net, 2022)
This research stems from a condition that occurs in all aspects of human life, namely covid-19. The existence of covid-19 all levels of education from elementary school to collage learn from home. Students are forced to learn from home because face to face learning is eliminated to reduce the spread of the corona virus or covid-19. This study aims to determine the role of parents in supporting children to learn English from home during pandemic covid-19 in district Binongko. This study is type of research qualitative. The techniques used in data collection is questionnaire. Based on the research conducted by the questionnaire that the ro le played by parents in supporting students to learn English from home, namely parents as role models, facilitator as motivator. As a motivator that can by parents can support students in learning English by motivating them in learn English.